ARTIFICIAL INTELLIGENCE IN LANGUAGE TEACHING: OPPORTUNITIES, CHALLENGES, AND PEDAGOGICAL IMPLICATIONS - AKBAROVA, Saidaxon Akmalxon qizi; ABDURAMANOVA, Diana Valerevna (The Lingua Spectrum, 2025)
Language learning is increasingly becoming infiltrated by AI technologies such as intelligent tutoring systems, automated writing evaluation, speech recognition and conversational agents. A systematic review of the literature during 2015-2024 indicates AI increases personalization, gives instantaneous suggestions and promotes the learners to interact actively. However, there are complex issues such as privacy, bias in algorithms and technology access gap, as well as teacher training that need to be addressed. This study concludes that AI can enhance language teaching in an ethically and strategically sound manner, which adds to the recent debate of what role AI might have within education, specifically with respect to language learning.